O jornalismo corsário de Pier Paolo Pasolini nos anos 1970 - Alves, Cláudia Tavares (2019)
Among all different literary and cinematographic activities developed by Pier Paolo Pasolini, his work in newspapers gained great importance with the general public and the critics because of the political intervention it represented. The purpose of this article is to search for means to comprehend the intellectual journey made by the Italian writer when he has written for a big mass media and to think about how these texts published in newspaper became part of the book Scritti corsari.Keywords: Pasolini; essayism; corsair journalism.